Clinical implication of tumour spread through air spaces in pathological stage I lung adenocarcinoma treated with lobectomy. (24th November 2020) - Yi, Eunjue; Lee, Jeong Hyeon; Jung, Younggi; Chung, Jae Ho; Lee, Youngseok; Lee, Sungho
Abstract: OBJECTIVES: The aim of this study was to evaluate the clinical implication of tumour spread through air spaces (STAS) as a prognostic factor in pathological stage I lung adenocarcinoma treated with lobectomy and to identify related parameters. METHODS: Medical records of patients who underwent pulmonary lobectomy for stage I (American Joint Committee on Cancers eighth edition) lung adenocarcinomas between 2012 and February 2018 at our institutions were reviewed retrospectively. Patients with minimally invasive adenocarcinomas and tumours ≥3 cm in size were excluded. Included patients were classified into STAS (+) and STAS (−) groups. Clinical implications of STAS and recurrence in patients were investigated. RESULTS: A total of 109 patients was analysed: 41 (37.6%) in the STAS (+) and 68 (62.4%) in the STAS (−) group. STAS was associated with larger consolidation diameter on chest tomography (≥1.5 cm; P  = 0.006) or a higher invasive ratio (≥85%; P  = 0.012) and presence of a micropapillary pattern in multivariable analysis ( P  = 0.003) The recurrence-free survival curve showed statistical difference ( P  = 0.008) with 3-year survival rates of 73.0% (9 patients) and 96.8% (2 patients) in the STAS (+) and STAS (−) group, respectively. However, no statistical significance was observed in the lung cancer-related survival curve ( P  = 0.648). The presence of STAS was an independent risk factor for recurrence in multivariable analysis (hazard ratio = 5.9, P  = 0.031). CONCLUSIONS: The presence of STAS could be an important risk factor for recurrence in patients with early-stage invasive lung adenocarcinoma treated with pulmonary lobectomy.